"Where did POTUS incite violence? Give me one quote." : Examining the role of social cognition in power abuse and in incitement to violence through critical discourse analysis - Okkonen, Laura (My University, 2022)
Manipulation, power abuse and incitement to violence in political discourse are not new phenomena as such. The introduction of social media platforms as tools for mass communication have, however, brought on unprecedented new challenges in restricting the spread of such phenomena. The main aim of this study was to understand how the invisible elements, or the socio-cognitive elements of discourse which imply manipulation and power abuse or worse yet, incitement to violence, can be identified, examined, and made more visible through critical discourse analysis. This study first introduced Critical Discourse Analysis (CDA) as a field of study, and some of the central methodologies and theories within CDA. The focus in the theoretical background was to introduce the basics of the socio-cognitive approach to CDA and to introduce the theoretical framework specifically focusing on power abuse and manipulation. The research methodology is based on the theoretical framework created by Teun Van Dijk, but also utilizes the research from other experts in the field, such as Norman Fairclough and Paul Chilton, where relevant. The data consisted of a written transcript on the President Trump speech in Washington D.C on January 6, 2021. This study was biased in the sense that it did not seek to answer whether power abuse, manipulation and incitement to violence occurred in the January 6th speech, but rather focused on how to identify such elements in discourse and how to make them more visible. The study concluded with a discussion on the findings and to ensure a triangulated element was included, it also examined the societal impacts of the role of such socio-cognitive elements in power abuse and incitement to violence. When analyzed using Teun Van Dijk’s theoretical framework, most, if not all of the socio-cognitive elements clearly indicating manipulation and abuse of power to incite the audience into violent action are present in President Trump’s speech on January 6th. The discussion therefore also elaborated on such related issues as accountability, regulation, and the role of social media in political discourse aimed at power abuse and incitement to violence. It appears clear that linguistics and more specifically, critical discourse analysts could potentially offer a valuable, if not critical contribution to the ongoing discussion on such things as harmful content online and the related regulation. Moreover, critical discourse analysis could serve as the basis to raise more awareness and understanding on what constitutes as hate speech and manipulation for the wider public at large. These issues could also benefit from further research in linguistics, as well as in political sciences and in legal studies.
Keywords: social cognition, manipulation, critical discourse analysis, power abuse